Advances in mixed-matrix membranes for biorefining of biogas from anaerobic digestion - Guerrero Piña, Jean Carlo; Alpízar, Daniel; Murillo, Paola; Carpio-Chaves, Mónica; Pereira-Reyes, Reynaldo; Vega-Baudrit, José; Villarreal, Claudia (Frontiers in Chemistry, 2024)
This article provides a comprehensive review of the state-of-the-art technology of polymeric mixed-matrix membranes for CO2/CH4 separation that can be applied in medium, small, and domestic biogas systems operating at low pressures (0.2–6 kPa). Critical data from the latest publications of CO2/CH4 separation membranes were analyzed, considering the ratio of CO2/CH4 permeabilities, the CO2 selectivity, the operating pressures at which the membranes were tested, the chemistry of the polymers studied and their gas separation mechanisms. And the different nanomaterials as fillers. The intrinsic microporous polymers (PIMs) were identified as potential candidates for biomethane purification due to their high permeability and selectivity, which are compatible with operation pressures below 1 bar, and as low as 0.2 bar. This scenario contrasts with other polymers that require pressures above 1 bar for operation, with some reaching 20 bar. Furthermore, the combination of PIM with GO in MMMs was found to not influence the permeability significantly, but to contribute to the membrane stability over time, by preventing the structural collapse of the membrane caused by aging. The systematic analysis here presented is a valuable resource for defining the future technological development of CO2/CH4 separation membranes for biogas biorefining.